Effect of Helicteres isora bark extracts on heart antioxidant status and lipid peroxidation in streptozotocin diabetic rats - Kumar, Ganesan; Banu, Gani Sharmila; Murugesan, Ganesan (Journal of Applied Biomedicine, 2008)
The present study investigated the effect of the aqueous extract of Helicteres isora L (Sterculiaceae) bark on oxidative stress in the heart of rats during diabetes. The aqueous extract of Helicteres isora bark (100 mg, 200 mg/kg body weight (b.w.)) was screened for its antioxidant effect in streptozotocin (STZ) induced diabetic rats. An appreciable decrease in peroxidation products, thiobarbituric acid reactive substances (TBARS), conjugated dienes (CD), and hydroperoxides (HP) was observed in the heart tissues of Helicteres isora (HI) treated diabetic rats. The decreased activities of key antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione-S-tranferase (GST) and glutathione (GSH) in diabetic rats were brought back to near normal range upon HI treatment. Tolbutamide was used as the standard reference drug. These results suggest that HI possesses promising antioxidative activity in STZ diabetic rats.
Keywords: streptozocin; experimentální diabetes mellitus; katalasa; Superoxide Dismutase; Malvaceae; Rats, Wistar; Catalase; slézovité; tolbutamid; superoxiddismutasa; rostlinné extrakty; Reactive Oxygen Species; peroxidace lipidů; Lipid Peroxidation; Tolbutamide; Plant Extracts; reaktivní formy kyslíku; Streptozocin; potkani Wistar; Diabetes Mellitus, Experimental